The effect of urea on the corrosion behavior of different dental alloys - Onur Geckili; Hakan Bilhan; Tayfun Bilgin; J Anthony von Fraunhofer (Wolters Kluwer Medknow Publications, 2012)
Objective: Intraoral corrosion of dental alloys has biological, functional, and esthetic consequences. Since it is well known that the salivary urea concentrations undergo changes with various diseases, the present study was undertaken to determine the effect of salivary urea concentrations on the corrosion behavior of commonly used dental casting alloys. Materials and Methods: Three casting alloys were subjected to polarization scans in synthetic saliva with three different urea concentrations. Results: Cyclic polarization clearly showed that urea levels above 20 mg/100 ml decreased corrosion current densities, increased the corrosion potentials and, at much higher urea levels, the breakdown potentials. Conclusion: The data indicate that elevated urea levels reduced the corrosion susceptibility of all alloys, possibly through adsorption of organics onto the metal surface. This study indicates that corrosion testing performed in sterile saline or synthetic saliva without organic components could be misleading.